A Balança comercial do Nordeste brasileiro: uma análise empírica - Damasceno, Mariana Gomes de Freitas (2003)
This dissertation is a presentation of practical studies based on statistics and other data of the International Trade Balance, imports and exports of North-East Region of Brazil --of which the three most import states are Bahia, Ceará and Pernambuco--, and of national economic from 1990 through 2001. The figures of foreign commerce of each individual state, of the whole region, and of the country as a whole, are measured and compared. The grade of openness of each of these economies is revealed. Through the method of Ordinary Minimum Squares (OMM) an estimate is made of the past impact of internal variables like price (exchange rates), local revenues (industrial production and ICMS), and external revenues (the USA index of Industrial Product and GNP) on the region’s ability to augment the volume of exports and imports.